2014
DOI: 10.1590/1981-6723.6013
|View full text |Cite
|
Sign up to set email alerts
|

Características físicas e nutricionais de pequis oriundos dos estados de Tocantins, Goiás e Minas Gerais

Abstract: ResumoO pequi é um fruto nativo do Cerrado que apresenta uma grande diversidade em suas características físicas e químicas. Estudos com frutos oriundos de diferentes ambientes de Cerrado são escassos na literatura. O objetivo deste estudo foi analisar as características físicas e nutricionais de frutos de pequizeiro oriundos dos estados de Tocantins (TO), Goiás (GO) e Minas Gerais (MG). Realizou-se a caracterização física de 30 frutos de pequi selecionados aleatoriamente, por estado, e determinou-se a composiç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
2
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 14 publications
5
28
2
12
Order By: Relevance
“…In relation to the number of putamen (NP), the mean values per mother tree (Table 03) are similar to data reported by Alves et al, (2014), who verified mean values of 1.3 for pequis from Minas Gerais and Tocantins and 1.5 for pequis from Goiás. Vera et al (2007) observed higher incidence of fruits with only one developed putamen.…”
Section: Physical Characteristicssupporting
confidence: 86%
See 1 more Smart Citation
“…In relation to the number of putamen (NP), the mean values per mother tree (Table 03) are similar to data reported by Alves et al, (2014), who verified mean values of 1.3 for pequis from Minas Gerais and Tocantins and 1.5 for pequis from Goiás. Vera et al (2007) observed higher incidence of fruits with only one developed putamen.…”
Section: Physical Characteristicssupporting
confidence: 86%
“…As for the weight (g) of the external mesocarp (MME), the mean values among mother trees (Table 03) are similar to values of Alves et al, (2014), who found fruits weighing between 53.8 and 343.9 g, with average value of 144.9 g, in the state of Minas Gerais. Considered as a residue, pequi skin (external mesocarp) is usually discarded, but it can serve as feed for grazing ruminants and used as bran in mixtures with silage and, or, replacement of elephant grass (GERASEEV et al, 2011).…”
Section: Physical Characteristicssupporting
confidence: 70%
“…Information on the physic-chemical characterization and nutritional value of the fruits of this biome represent a stimulus to the knowledge, the consumption and the application in the pharmaceutical and food industries, besides contributing to the conservation of the Cerrado, since predatory and unsustainable exploitation stands out in the local, threatening the survival of the species (Silva et al, 2008;Alves et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is an important source of nutrients, whose pulp has about 3.73 ± 0.01 g per 100 g of proteins; 26.15 ± 0.85 g per 100 g of lipids; 58.83 ± 2.06 mg per 100 g of calcium; 1.40 ± 0.59 mg per 100 g of iron and 2.81 ± 0.70 mg per 100 g of zinc. 18 It also contains bioactive compounds with antioxidant properties, such as vitamin C (6.63 ± 1.02 mg per 100 g), 19 phenolic compounds (1.80 ± 0.04 to 3.34 ± 0.07 mg GAE g -1 ) and total carotenoids (37.08 ± 1.84 to 187.00 ± 12.43 µg g -1 ). 20 Violaxanthin, lutein and zeaxanthin are among the predominant carotenoids observed.…”
Section: Introductionmentioning
confidence: 99%